2016
DOI: 10.1080/17457300.2016.1177551
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pedestrian countdown signals on single and two vehicle motor vehicle collisions: a quasi-experimental study

Abstract: The objective of this study was to examine the impact of pedestrian countdown signals (PCS) on the rate of motor vehicle collisions (MVCs) in Toronto, Canada. A quasi-experimental design was used to compare rates of single and two vehicle MVCs before and after installation of PCS in Toronto, Canada between January 2005 and December 2009. Collision incidence rates were compared using Poisson regression analyses with adjustment for relevant cofounders and reported as incidence rate ratios (IRR) with 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, when PSCTs were used in India [73] and China [76], the number of pedestrianto-vehicle conflicts was more significant. Canadian studies [83] showed that PSCTs increased the number of all crashes with pedestrians by 7.5%. There was no significant influence on the number of crashes with injuries or fatalities.…”
Section: Pedestrian Safety (Vehicle-pedestrian Conflicts)mentioning
confidence: 98%
“…However, when PSCTs were used in India [73] and China [76], the number of pedestrianto-vehicle conflicts was more significant. Canadian studies [83] showed that PSCTs increased the number of all crashes with pedestrians by 7.5%. There was no significant influence on the number of crashes with injuries or fatalities.…”
Section: Pedestrian Safety (Vehicle-pedestrian Conflicts)mentioning
confidence: 98%
“…Another study investigated the effectiveness of PCS on car-car collisions in 2016 in Toronto, Canada and found that the single or two-vehicle MVC incidence rate increased 7.5% with the introduction of PCS. This negative effect on collisions was postulated to be due to changes in driver behaviour related to increasing vehicle speeds to pass through the intersection, or by coming to a sudden stop before entering the intersection in response to the PCS 19. Other studies done on a much smaller scale of selected intersections reported declines in collisions after PCS installation 15 16…”
Section: Introductionmentioning
confidence: 99%